Assessing the spatial accessibility of microfinance in northern Bangladesh: a GIS analysis - Khan, Akib; Rabbani, Atonu (© 2015 Blackwell Publishing Inc., 2017)
This article was published in Journal of Regional Science [ © 2015 Blackwell Publishing Inc.] and the definite version is available at: https://goo.gl/VBtA8W